Magnetic resonance imaging appearances of recurrent cervical carcinoma. Issue 3 (1st May 2007) - Babar, S.; Rockall, A.; Goode, A.; Shepherd, J.; Reznek, R.
Abstract : Our aim was to describe the patterns of disease recurrence and residual disease in patients treated for cervical carcinoma and to evaluate imaging features, which can help to differentiate recurrence and/or residual disease from posttreatment change. In a retrospective observational study, magnetic resonance imaging (MRI) scans of 48 patients with recurrent or residual cervical carcinoma were reviewed by two radiologists. Sixteen patients had undergone primary surgical treatment and 32 were treated by chemoradiotherapy. Recurrence was confirmed by histology (28), clinical and radiologic progression (6), and by patient death (14) due to progressive disease. Magnetic resonance images were analyzed for the site of recurrent/residual disease, signal characteristics, and invasion of adjacent structures. There were 29 recurrences, while 19 patients had residual disease. Most of the recurrences (70.4%) occurred within the first year of the start of treatment. Recurrent disease was confined to the central axis of the cervix in six patients following chemoradiotherapy and to the vaginal cuff in three of these patients following surgery. The recurrent tumor was isointense to the adjacent muscles on T1-weighted sequence in 95.3% and hyperintense on T2-weighted in 88.9%. The cervix was involved in every case of residual disease and in 10 of 29 (34.5%) patients with recurrent disease. Recurrent disease was present in the vaginal cuff in 14 of 16 (87.5%) postsurgical patients. Parametrial invasion was present in 13 (81.3%) patients treated surgically and in 22 (68.8%) of those receiving chemoradiotherapy. Involvement of the uterosacral ligaments was seen in 8 (57.1%) surgical patients and 14 (43.8%) nonsurgical ones. Bladder invasion was seen in four (25.0%) patients treated surgically and three (9.4%) of those treated with chemoradiotherapy. Radiotherapy change within the marrow was seen in 13 (27.0%) patients in total, whereas bone metastases were present in 4 (8.3%) patients. Recurrent cervical carcinoma can present with varied imaging features. Knowledge of the patterns of recurrence can aid early detection and may determine further therapeutic options.